The world of Wu Zhao : annotated selections from Zhang Zhuo's Court and country - Rothschild, N. Harry (Anthem Press, 2023)
The World of Wu Zhao is an annotated translation of Zhang Zhuo's collection of miscellany, Court and Country, that offers a lively, folksy and novel perspective of the empire of Wu Zhao, China's first and only female emperor, that will amuse and shock readers, prompting them to recalibrate everything they think they know about medieval China.